THE ARTICLE CONSIDERS THE ACCOUNT FOR THE REINFORCED CONCRETE HOLLOW - SECTION ELEMENTS WITH NORMAL CRACKS IN TORSION - Azizov, T. N.; Melnik, A. V.; Melnik, A. S. (Science and Transport Progress, 2010)
The article is dealt with the methodology of determination of stressed-and-strained state for the reinforced concrete hollow-section elements with normal cracks as a result of torque rigidity. It is shown that the inflexibility of elements of bridges and frameworks influences significantly upon the redistribution of efforts between them.